2013
DOI: 10.1186/1471-230x-13-45
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a probiotic ‘functional food’ in the management of irritable bowel syndrome

Abstract: BackgroundIrritable Bowel Syndrome (IBS) is a common condition characterised by pain, distension and altered bowel habit. Evidence suggests functional foods containing probiotics improve gastrointestinal transit, however, data are limited by short follow-up periods and evaluation in selected populations.MethodsA multi-centre, randomized, double blind, controlled trial to evaluate the effect of a probiotic vs non-probiotic dairy product on symptoms in IBS with a constipation element (IBS – Constipation or IBS –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 39 publications
1
91
1
3
Order By: Relevance
“…One study included patients with functional gastrointestinal disorders, ie, with diarrhea but not constipation and not necessarily suffering from abdominal pain, 72 one was restricted to constipation predominant IBS (IBS-C) patients 65 and 4 included only diarrhea predominant IBS (IBS-D) patients. 62,68,69,80 All studies claimed the use of Rome (II or III) criteria, nevertheless, a more detailed description of the patient population (the number of IBS-D, IBS-C, and mixed IBS [IBS-M] patients) was lacking.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study included patients with functional gastrointestinal disorders, ie, with diarrhea but not constipation and not necessarily suffering from abdominal pain, 72 one was restricted to constipation predominant IBS (IBS-C) patients 65 and 4 included only diarrhea predominant IBS (IBS-D) patients. 62,68,69,80 All studies claimed the use of Rome (II or III) criteria, nevertheless, a more detailed description of the patient population (the number of IBS-D, IBS-C, and mixed IBS [IBS-M] patients) was lacking.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…48 One study did not differentiate IBS-C from constipation. 52 Sample sizes varied between 7 38 and 1348, 25 exceeding 100 in 10 of the publications (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…27,40 One additional study reported slightly higher rates of discomfort in a placebo-treated cohort. 48 …”
Section: Pain Intensity Ratingsmentioning
confidence: 99%
“…En ambos trabajos concluyeron que se observa una mejoría clínica significativa luego del consumo de probióticos, teniendo en cuenta el dolor abdominal y diarrea al comparar con el consumo de placebo (27)(28)(29)(30)(31)(32). La Tabla 1 resume los hallazgos de los estudios clínicos incluidos en los metaná-lisis previamente mencionados.…”
Section: Síndrome De Intestino Irritableunclassified
“…con una mejoría clínica hasta de 80% en pacientes tratados (15,17,34,37). En cuanto al SII, en la mayoría de artículos estudiados se establece una asociación entre el consumo de probióticos y la mejoría subjetiva y objetiva de sus síntomas cardinales, valorados tanto por cuestionarios subjetivos como por la escala de Bristol (calidad de deposiciones) (13,17,32).…”
Section: Conflictos De Interésunclassified